STUDY OF MURAL ART STYLE IN PUBLIC SPACES OF THE HYSTERIA COMMUNITY IN SEMARANG - Hermalita Siwi, Vini (Arty: Jurnal Seni Rupa, 2025)
This study aims to analyze the style, values, meaning, and educational function of the mural works of the Hysteria Community in public spaces in the city of Semarang, while also examining the public's acceptance of the social messages conveyed through these murals. A qualitative approach was used through observation, interviews, and documentation of two major works: "Tulang Lunak Bandeng Juwana" (2024) and "Doa Kuat!" (2025). Roland Barthes' semiotic analysis was used to interpret denotative and connotative meanings, while John Fiske's theory assessed how visual elements work at the levels of reality, representation, and ideology in shaping public understanding. The results of the study show that Hysteria utilizes local cultural symbols, visual metaphors, and color compositions to present communication that is not only aesthetic but also educational through a process of social awareness (PSR). Messages about adaptation, resilience, solidarity, and self-reflection are presented to encourage public engagement in understanding the dynamics of the city and the social issues that are inherent to it. Both murals serve as a medium for social learning that strengthens Semarang's cultural identity and builds a dialogical relationship between artists, the community, and public spaces.